2022
DOI: 10.1001/jamanetworkopen.2022.28008
|View full text |Cite|
|
Sign up to set email alerts
|

Incubation Period of COVID-19 Caused by Unique SARS-CoV-2 Strains

Abstract: IMPORTANCESeveral studies were conducted to estimate the average incubation period of COVID-19; however, the incubation period of COVID-19 caused by different SARS-CoV-2 variants is not well described. OBJECTIVE To systematically assess the incubation period of COVID-19 and the incubation periods of COVID-19 caused by different SARS-CoV-2 variants in published studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
156
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(208 citation statements)
references
References 150 publications
11
156
0
Order By: Relevance
“…One of them was the study of Du et al [14], which reported an estimated median incubation period of 3.4 (slightly higher than our estimate) and 3.1 days for Delta and Omicron variants, respectively. Furthermore, a systematic review performed by Wu et al [15] estimated a median of 4.4 and 3.4 days for these same variants.…”
Section: Discussionmentioning
confidence: 94%
“…One of them was the study of Du et al [14], which reported an estimated median incubation period of 3.4 (slightly higher than our estimate) and 3.1 days for Delta and Omicron variants, respectively. Furthermore, a systematic review performed by Wu et al [15] estimated a median of 4.4 and 3.4 days for these same variants.…”
Section: Discussionmentioning
confidence: 94%
“…A transmission line list was constructed by linking infected contacts to their reported index case if a positive test occurred in the 21 days before or after their index case tested positive. 14 If not, trans-mission between these individuals was deemed very unlikely and the pair was only kept in the contact line list. For non-positive contacts, we had no information on whether they tested negative or were not tested.…”
Section: Contact and Transmission Patternsmentioning
confidence: 99%
“…Methods for the detection of viral infection, as well as vaccines and therapeutics, have improved the situation; however, continuous viral mutations, especially in low-vaccinated geographical regions [ 2 ], have led to the emergence of new variants at different locations and times across the world. These variants show distinct characteristics with respect to incubation times, infection routes, and severity of the disease [ 3 ]. This has posed serious challenges at multiple levels including a) medical intervention by healthcare workers [ 4 ]; b) detection of new strains carrying new genetic mutations in the population by clinical labs; c) vaccine efficacy for pharmaceutical companies [ 5 , 6 ], and d) monitoring of the temporal and geographical course of the pandemic for the scientific community [ 7 ].…”
Section: Introductionmentioning
confidence: 99%